Modeling and Analyzing the Impact of the Internet of Things-Based Industry 4.0 on Circular Economy Practices for Sustainable Development: Evidence From the Food Processing Industry of China - Sun, Xiaoli; Wang, Xuan (Frontiers in Psychology, 2022)
The industry 4.0 concept proposes that new cutting-edge technologies, such as the Internet of Things (IoT), will grow. The acceptance of IoT in the circular economy is still in its infancy, despite its enormous potential. In the face of growing environmental affairs, Internet of Things (IoT) based Industry 4.0 technologies are altering circular economy (CE) practices and existing business models, according to the World Economic Forum. This research investigates the function of IoT-based Industry 4.0 in circular CE practices, as well as their impact on economic and environmental performance, which in turn influences overall organizational performance. China-based enterprises provide information for the study, which includes data from 300 companies. Utilizing a structural equation modeling framework known as partial least squares structural equation modeling (PLS-SEM). The major findings are presented in the study: (I) The IoT significantly improves the activities of the circular economy; (II) The IoT significantly improves the practices of the circular economy; and (III) The IoT meaningfully advances the practices of circular economy (green manufacturing, circular design, remanufacturing and recycling). Moreover, the findings show that environmentally-friendly business practices help enhance environmental performance of firm, while also stimulating their economic performance; and improved environmental performance has a significant positive influence on firm performance. This research lays the groundwork for contributing nations/companies to attain economic and long-term sustainability goals at the same time by incorporating Internet of Things (IoT)-based Industry 4.0 technology into circular economy practices.